Language Situation in Ukraine and Possibilities of Teaching the Transcarpathian Geographical Heritage Through English - Fodor Gyula; Фодор Дюло (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-Grafika, 2015)
Abstract. The abundance and richness of the local Transcarpathian geographical heritage is unquestionable, in terms of natural and social science as well. Natural conditions and resources of the region play a crucial part in the quality of life of the local society and are very important from the point of view of the growing tourist industry, one of the potential leading branches of the county’s economy. That makes substantial to properly teach about this heritage in English (as presently the most popular foreign language in the region) to the local, mainly Hungarian-speaking teenagers. Though, to fulfill this task is not easy, among others owing to the sometimes inappropriate traditional Soviet and partly post-Soviet approach to foreign language teaching, which is not always based on functionality and usability. We believe that teaching correct geographical technical language will serve as a step on the way of reforming this outdated approach in general.
Мовна ситуація в Україні та можливості викладання географічної спадщини Закарпаття через англійську мову
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00000939
Keywords: geographical heritage; lingua-ethnic groups; non-native language; cultural focus